Women and psychological trauma of 9/11 in Amy Waldman’s The Submission - Zabihzadeh, Seyedeh Robabeh; Ruzy Suliza Hashim,; Raihanah M. M., (Penerbit Universiti Kebangsaan Malaysia, 2017)
On September 11, 2001, the world was stunned into silence as four hijacked airplanes crashed into two of America’s iconic landmarks, namely the World Trade Centre and the Pentagon. For the first time, perhaps since the Vietnam War, the entire United States of America was engulfed in a mutual sense of loss and inconsolable grief. 2996 people, a vast number of them unarmed civilians including all the passengers aboard the four hijacked airplanes, lost their lives in what was perceived by many to be the worst terrorist attack of the twenty-first century. Occurrence of such a colossal tragedy has led to producing a large corpus of textual representation of the event including countless novels such as Amy Waldman’s The Submission (2012). This study focuses on analysing The Submission by Amy Waldman using the theory of Psychoanalysis to explore the concept of psychological trauma and the effects of PTSD (Posttraumatic Stress Disorder) on female characters affected by the tragedy of 9/11. The analysis, which is mostly based on Wilson and Keane (2004) and Caruth (2001) psychoanalysis theories, seeks to explore Waldman’s perception of the process of healing from the devastating tragedy and psychological trauma of the female characters of the story. It is believed that Waldman’s novel does not only portray the trauma of the characters but also presents the path of recovery and overcoming the PTSD of those who were emotionally wounded by the tragedy of 9/11.